Two new cave rnicolous genera of Julidae (Diplopoda, Julida), with notes on the tribe Brachyiulini and on julid subanal hooks and anchors - Akkari, Nesrine (Pensoft Publishers, 2011)
Abstract. Two remarkable genera and species of the millipede family Julidae, Titanophyllum spiliarum gen. n., sp. n. and Mammamia profuga gen. n. sp., n., are described from caves in Greece and Italy, respectively. The presence of a flagellum and the absence of a ‘pro-mesomerital forceps’ on the gonopods place them in the tribe Brachyiulini Verhoeff, 1909, an unnatural grouping based on plesiomorphic characters. Both are outstanding in being the only hitherto known blind julidans having such gonopodal features. A dichotomous key to the nine valid brachyiulinine genera based on peripheral and gonopodal characters is presented. Moreover, notes on subanal hooks and anchors in Julida are provided with hypotheses on their possible function.